Investigation of sensitive elements of temperature transducers based on thermometric material Lu1-xScxNiSb - Pashkevych, Volodymyr; Krayovskyy, Volodymyr; Haranuk, Petro; Romaka, Volodymyr; Stadnyk, Yuriy; Romaka, Lyubov; Horyn, Andriy (Видавництво Львівської політехніки, 2022)
The results of experimental studies of sensitive elements of temperature transducers based on semiconductor thermometric material Lu1-xScxNiSb, x = 0.01–0.10, are presented. Thermometric materials Lu1-xScxNiSb were made by fusing a mixture of components in an electric arc furnace with a tungsten electrode (cathode) in an atmosphere of purified argon under a pressure of 0.1 kPa on a copper water-cooled hearth (anode). Heat treatment of alloys consisted of homogenizing annealing for 720 h in vacuumed to 1.0 PA at a temperature of 1073 K. Arrays of diffraction data of X-ray diffraction studies were obtained on a powder diffractometer STOE STADI-P, and using the program Fullprof calculated structural characteristics. The chemical and phase compositions of the samples were monitored by metallographic analysis (scanning electron microscope Tescan Vega 3 LMU). The basis of the sensitive element of the resistance thermometer on Lu1-xScxNiSb materials is polycrystalline samples in the form of rectangular parallelepipeds with a size of 0.5×0.5×5 (mm3), to which the contacts are made of copper and/or platinum wire. Experimental measurements of electrical resistance values were performed using the four-contact method, and the values of the thermopower coefficient by the potentiometric method concerning copper and/or platinum. The thermoelectric pair platinumthermometric material was the basis of the thermoelectric converter. Modeling of thermometric characteristics of sensitive elements of the thermometer of resistance of the thermoelectric converter is carried out by a full potential method of linearized plane waves (Full Potential Linearized Augmented Plane Waves, Elk software package). The results of experimental measurements served as reference currents in modeling the characteristics.X-ray phase analysis showed the homogeneity of the studied samples of thermometric materials Lu1-xScxNiSb, as evidenced by the absence of traces of extraneous phases on the diffractograms. The dependences of the period of the unit cell a(x) Lu1-xScxNiSb are not linear, which indicates more complex structural changes than the one-act substitution of the Lu atom by Sc. Measurements of the values of the specific magnetic susceptibility χ (T, x) were performed by the relative Faraday method at T = 273 K using a thermogravimetric installation with an electronic microbalance EM-5-ZMP in magnetic fields up to 10 kGs. Experimental studies of the specific magnetic susceptibility of χ(x) sensitive elements have shown that the samples at all concentrations are Pauli paramagnetics, and the value of χ(x) is determined by the electron gas. In this case, the values of the magnetic susceptibility χ(x) are proportional to the density of electronic states at the Fermi level g(εF). In the area of concentrationsx = 0–0.02, the values of magnetic susceptibility χ(x) undergo insignificant changes, which indicates small changes in the concentration of current carriers. At a concentration x > 0.02 there is a rapid increase in the density of electronic states at the Fermi level g(εF), indicating an increase in the concentration of free current carriers. The presence of high-temperature activation sites on the temperature dependences of the resistivity ln(ρ(1/T)) for all Lu1- xScxNiSb samples indicates the location of the Fermi level εF in the band gap εg of the semiconductor, and positive values of the thermopower coefficient α(T) specify its position – near the valence band εV. The main carriers of electric current are holes. The nature of the behavior of the resistivity ρ (x, T) Lu1-xScxNiSb at all temperatures also corresponds to the results of modeling the kinetic properties. The fact that in the range of concentrations x = 0–0.04 the values of the resistivity ρ (x, T) Lu1-xScxNiSb change slightly at all temperatures indicates a significant advantage of the concentration of holes over electrons. This is indicated by positive values of the thermopower coefficient α (x, T). At concentrations x ≥ 0.04, the resistivity increases rapidly, which is due to the appearance of donors, which partially compensate for the acceptors, which reduces the concentration of free holes, and, as a result, we have an increase in the resistance. The behavior of the thermopower coefficient α (x, T) Lu1-xScxNiSb is adequate. The appearance and increase in the electron concentration are accompanied by an increase in the thermopower coefficient α (x, T). At a concentration of x ≈ 0.07, the dependence of the thermopower coefficient contains an extremum, and then the values of the thermopower coefficient rapidly decrease at a temperature of T = 80 K and concentrations at x ≈ 0.1. Electrons are already the main current carriers. This is indicated by the negative values of the thermopower coefficient. It was experimentally established that at the concentration range x = 0–0.07 the Fermi level velocity εF from the valence band εV is ΔεF/Δx = 4.9 meV /% Sc, and at the concentration, x ≥ 0.07 – ΔεF/Δx = 11.2 meV /% Sc. The presence of a difference in the velocities of the Fermi level εF indicates different rates of generation of acceptors and donors: at a concentration of x ≥ 0.07, the concentration of donors increases ~2 times faster than at the site x = 0–0.07. The functions of conversion of sensitive elements of resistance thermometer and thermoelectric transducers in the temperature range 4.2–1000 K are modeled. The ratio of the change in the values of the thermopower coefficient to the range of temperature measurements in thermocouples is greater than all known industrial thermocouples. In addition, the temperature coefficient of resistance (TCR) of the obtained resistance thermometers is higher than the TCR of metals but is inferior to the value of TCR of sensitive elements made of traditional semiconductors. At the same time, none of the known resistance thermometers based on traditional semiconductors provides stable characteristics at temperatures of 4.2÷1000 K.
Keywords: Electric conductivity; Thermopower coefficient; Fermi level